2017
DOI: 10.14238/pi14.1-2.1974.11-20
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of Neonatal Convulsions

Abstract: The purpose of this paper is to review and evaluaute the clinical dataon incidence, sex, body-weight, morbidity and mortality and the possible etiology of convulsions occurring in the neonatal period (i.e. the first 30 days of life) and to study the outcome in follow up examination at the age of more than 6 months. The age of 6 months is taken as a limit because previous experiences and those of other authors (Billing, 1964) have shown that only after the age of 6 months neurological and mental disorders remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Most neonates were full-term with birth weight of more than 2500 grams. The result was comparable with the study reported by Hendarto et al ,9 in which, girls were outnumbered boys, and the range of birth-weights was 2500-3500 grams. This study showed that the incidence of neonatal seizures in CM Hospital was 0.9%, in Harapan Kita Hospital was 0.3% (5/1559), and in Fatmawati Hospital was 0.3% (2/588).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most neonates were full-term with birth weight of more than 2500 grams. The result was comparable with the study reported by Hendarto et al ,9 in which, girls were outnumbered boys, and the range of birth-weights was 2500-3500 grams. This study showed that the incidence of neonatal seizures in CM Hospital was 0.9%, in Harapan Kita Hospital was 0.3% (5/1559), and in Fatmawati Hospital was 0.3% (2/588).…”
Section: Discussionsupporting
confidence: 90%
“…3,[6][7][8] A previous study in Jakarta (1971) reported that the prevalence of neonatal seizures in Cipto Mangunkusumo (CM) Hospital was 0.7%. 9 The diagnosis of neonatal seizures is difficult to establish due to its form that mimics normal movements. To recognize the type or form of neonatal seizures is im-portant because it might be the only sign of CNS disorders.…”
mentioning
confidence: 99%